(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines the pedagogical potential of the nature corner in the education and upbringing of preschool and primary school children. The nature corner is considered not merely as a decorative element of the educational environment, but as an important pedagogical space that contributes to children’s cognitive activity, ecological culture, aesthetic perception, labor skills, responsibility, and social-emotional development. The article analyzes the educational significance of children’s direct interaction with nature, caring for plants, working with natural materials, observing natural phenomena, and conducting simple experiments. It also reveals the possibilities of forming kindness, carefulness, observation skills, independent thinking, and ecological responsibility through activities organized in the nature corner. The study uses methods of pedagogical observation, theoretical analysis, comparison, and generalization. At the end of the article, methodological recommendations are provided for the effective organization and use of the nature corner in educational practice.